Persistent Recidivists in the Light of Criminological and Psychological Resaearch (Archives of Criminology, 1976)
This work presents the findings of studies of offenders, whose offences were time and again revealed, who had been frequently tried and many times been imprisoned. Studies were made of prisoners, convicted at least four times and who found themselves in prison at least for the fourth time, being of the age between 26—35 (the average age being 31). Studies were conducted in 1965—1966 in the Warsaw Central Prison. Selected from among the 440 prisoners there at that time, whose age and recidivism was in accordance with the above mentioned criteria, were those, who had domiciles in Warsaw or the voivodship of Warsaw and who possessed closest family members (as a rule father or mother), who could supply information about them. Making the successsive selection for studies, efforts were nevertheless made to take into account in the studied group those persistent recidivists who were convicted of robbery; this was due to the intention to take into account all the cases of recidivism, involving more serious offences. In connection with this departure from the principle of random samples, this group contained considerably more offenders convicted of robbery than was the case in the remaining group of persistent recidivists which was not subject to thorough investigation. The subject of thorough studies were half of the persistent recidivists, which at the time under discussion, were inmates of the Warsaw Central Prison, namely 220 prisoners.Studies concentrated on: collection of data about the convictions of the offenders, checking at the juvenile court records, whether they had been brought before a court while they were minors, collection of extracts from court records (regarding the most recent as well as prior convictions), efforts to obtain, by means of interviews and questionnaires, information about the work of the studied persons in various enterprises, where they had been employed, the drawing up of extracts from prison records, collection of medical documents of those prisoners who had received treatment in psychiatric outpatient clinics, in anti-alcoholic outpatient clinics or who had been in psychiatric hospitals; interviews conducted with the closest family members of the offenders, psychological examinations conducted with the prisoners of the group selected for studies (psychological interviews, the Wechsler-Bellevue scale, Sachs’s and Levy’s SentenceCompletion Test, the Minnesota Multiphasic Personality Inventory (MMPI) and the Buss-Durkee inventory). In addition to this 60 recidivists underwent psychiatric examinations. The studies were conducted by a team with the participation of Professor S. Batawia, who also headed the entire research; in the work of the team participated in addition to the author of this article: M. Kiezun- Majewska, S. Szelhaus and D. Wojcik. ; The average number of convictions per recidivist amounted to 6.5; the average number of stays in prison to 6.0. A persistent recidivist committed on an average 10.1 offences for which he was convicted, of these: 6.8 offences against property, 3.0 offences against the health or public authorities and offices as well as 1.3 other offences. One of the striking features of the offences committed by multiple recidivists was the variety of their offences: as many as two-thirds were convicted of offences of various types, only 27% were convicted exclusively of offences against property and a mere 9% were convicted exclusively of offences against the health as well as against the authorities and public offices. What is striking even in the case of those who were convicted exclusively of offences against property, is the heterogeneous nature of their offences and the lack of specialization in this respect. Violent offences (against the health or public authorities and offices) were committed by the overwhelming majority of those studied (71%). Almost all of the offences, and also the majority of the robberies were committed while they were intoxicated. Persistent recidivists are relatively rarely convicted of serious offences. Only 12.5% of those investigated could be considered dangerous because of frequent serious violent offences (including also robbery) and besides this only 12% could be qualified as people causing serious material damage. According to statistics concerning the whole of Poland every twenty-fifth persistent recidivist only was in 1973 convicted of an offence qualified according to the penal code as a felony (statutory minimum of punishment - 3 years). According to this study, a typical persistent recidivist is a person whose offences have caused not only social damage, but also serious damage to the perpetrators themselves, because the offences committed as a rule did not bring him any greater material advantages, but gave rise to consequences, due to which he spent a considerable part of his life in prison: 69% spent after the age of 17 more time in prison than out of prison. Almost half of them were less than a year at liberty between two successive convictions.These studies aimed at obtaining the possibly most allround information about the persistent recidivists and about their life histories. Special stress was laid on the problem of the early maladjustment of these people and the age when their first offences were committed, their professional work and attitude to their family, on the very essential problem of habital excessive drinking on their part, and also on personality disorders.Information on the family milieu from which the prisoners indicates that the majority of their fathers (77%) worked systematically (mainly as unskilled workers) and a mere convicted. However, fathers drinking to excess were a serious problem in the families of the sampled prisoners. When the prisoners were children approximately 27% of the fathers were heavy drinkers, in addition 25% were alcoholics. It is also interesting that alcoholism was found with almost half of the families of the parents of the investigated prisoners, involving their fathers or brothers. The social behaviour of the mothers of the sampled group was more positive. While half of the fathers were considered socially negative (due to excessive drinking, frequent convictions or unsystematic work), only 16% of the mothers deserved such an opinion. About 10% of the mothers drank systematically to excess, 6% had been convicted and 3% were suspected of being prostitutes. Only 41% of the recidivists lived, while being minors, within a complete family, in the cases of 48% of the families one of the parents had died (most frequently the father); in half of the cases the family was broken up when the studied prisoners were below 15 years. Connected with a disturbed family structure were changes regarding the educational milieu. 40% of the group changed their homes in their childhood, in the case of about one-fourth of them many changes were found: they brought up at least in three different homes. The marital relations of the prisoners’ parents were often (50%) very bad. The frequent breaking up of the family and work of the mothers to earn a living was often combined with the neglect of the children, found in as many as two-thirds of the families of the recidivists. On the basis of statements made by the studied group and their mothers the material conditions during their childhood were in 55% of the families very difficult, preventing the satisfaction of the most basic needs. The sampled recidivists relatively frequently came from families with many children: in 38% of the cases these were families with at least four children, in 21% these were families with three children. The brothers and sisters of the recidivists often, just as the latter themselves, had gaps in their primary school education (in 39% of the families there are found among the brothers and sisters persons who have not finished primary school education) and also had similar shortcomings regarding professional skills (over half the brothers had no vocational training at all). But the recidivists who were studied also had (though only in few cases) brothers and sisters by far outdistancing them as regards education. In as many as two-thirds of the families itwas found that there were socially maladjusted brothers; in 44.5% of the families somebody from among the siblings had committed theft, had been brought before a court, while still being a minor, or had been convicted after having reached the age of 17; in as many as one-third of the families brothers were recidivists. The negative educational ditions in the families of the recidivists thus found their reflection in substantial social maladjustment of their brothers and sisters. The intensification of this maladjustment was, however, with the sampled group higher than was the case with their brothers, only one-fifth were families where all the brothers were recidivists.  Studying the extent to which the sampled individuals were sociallymaladjusted While being juveniles, questions were asked during interviews regarding their early childhood. According to data obtained from mothers, neurotic symptoms could be noticed in many of the sampled recidivists (two-thirds). Though the percentage of those who showed such symptoms during the school period was slightly smaller (58%), there nevertheless were still many with such symptoms as bed-wetting(13%) and stuttering (17%). Half of the studied group of recidivists, who showed neurotic symptoms in school, displayed a number of such symptoms.During the investigation in prison 58% of the respondents admitted some neurotic symptoms, mainly disturbances of sleep and special fears. Striking was the frequent fact of stuttering (16.5%), found during inations in prison (on the basis of observation). A large group of persistent recidivists revealed a striking durability of neurotic symptoms from their childhood on till adulthood.Half of the recidivists of this group were defined by their mothers as ‘’difficult to bring up” during childhood (very disobedient and stubborn), while 44% were much more aggressive than the other children in the family. The childhood of the recidivists was marked by considerable disturbances at school: 16% of them finished no more than 3 grades of primary school, 25% —4—5 grades and 15% — 6 grades. A total of as many 56% did not finish primary school education. These shortcomings in primary school education were found especially often with those individuals among the group who had a lower IQ (IQ below 91), and those who had been brought up in negative family milieux, as well as those whose school years were during the war period and those who had revealed early social maladjustment.  Two-thirds of this group of recidivists repeated the same class in school, 44% systematically played truant, in many cases (60%) it was found that the teachers had complained about their behaviour in school. While still being minors 41% of them had run away from home. Two-thirds maintained that during their childhood they spent much time outside their home, running the streets in the company of colleagues, who were stealing and drinking alcohol. Worth special attention is the fact, that close to half of the sampled group (46.8%) began already as minors to drink alcohol to excess, and there is information regarding 22%, indicating that when being barely 13—14 years old, they already were drinking wine or vodka at least once a week. On the basis of interviews and information obtained from juvenile court records, it was found that at least 36.2% of the recidivists from this group faced courts at an age below 17, while 21.3% were sent toapproved schools. Taking into account also additional information regarding theft that was not found out, it has appeared that as many as at least 57% of the persistent recidivists were stealing or brought before a court while they were still under age. They belong to the category of former juvenile delinquents who are recidivists and whose offences are of a most persistent nature.Those recidivists whose delinquency started while they were still adolescents, more frequently than the remaining ones, came from negative family milieux. In interviews and tests results more frequently data found among them testifying to personality maladjustment: aggressiveness during school attendence and aggressiveness during the period when these studies were conducted (found on the basis of the opinions of psychologists and questionnaires according to the Buss-Durkee inventory, MMPI profiles with a markedly raised F scale).In addition to those of the group who committed offences while minors, there were still 53 (25%) of them who, though they had, as it was found, not committed offences at that time, nevertheless revealed considerable social maladjustment. Only in the case of 17% of the recidivists studied, no such symptoms were found. These recidivists were during the period when the studies were conducted in many respects better than the remaining ones: they more often possessed professional skills, had worked more systematically, more rarely been in prison and had longer intervals between the successive convictions. The first convictions of these individuals after the age of 17 started later, more among them had their first trials only after the age of 21. But as regards alcohol drinking they did not differ from the other recidivists. This is a very important fact, since in the genesis of offences committed by recidivists who as minors had not shown symptoms of social maladjustment, drinking of alcohol in excess played a larger role than was the case with the remaining recidivists and the entire character of the offences committed by them later was connected with habitual drinking of alcohol.Recidivists in whom no symptoms of social maladjustment were found while they were adolescents, nevertheless came, just like the remaining recidivists, relatively frequently from negative family milieux and often data were found concerning them, which pointed to early personality disorders; thus they were especially susceptible to unfavourable social conditions. In the life histories of these recidivists can be clearly noticed the significance of unfavourable situations for the genesis of their delinquency; the lasting aspect of this delinquency is later combined with alcoholism and difficulties encountered in the social functioning of individuals, who have already been in prison. Data from the juvenile period of persistent recidivists indicate that they entered adult society already with substantial gaps in their education, without the habit of systematic work and without any vocational training. Only three from among the studied group had finished vocational school, and at the time the study took place 55% had no professional qualifications whatsoever.This lack of vocational skill was especially often typical of those, who in connection with their lower intelligence quotient had objective difficulties at school, were lacking sufficient motivation to learn a trade and those, who had stayed at liberty only for a very short period.The studied group started to work at an early age (41% already below 16), which was connected with their difficult material conditions and the early dropping out from school. When being young adults half of the sampled group had worked relatively systematically (at least during half the period they stayed at liberty and were able to work). Later in their life can be noticed a distinct decline in systematic work. During their last stay at liberty 43% did not work at all; among the remaining individuals, 40% of those who started to work, were longer without work than with work. During the entire period since they reached the age of 17 only one-third of them worked more than half the time they actually could have worked, while the majority worked very little, of these 35% less than 25% of the time they would have worked. Unsystematic work was often combined with certain* personality traits of these individuals, such as agressiveness and inability to submit to discipline combined with a lack of professional qualifications and also with social derailment.In 30% of the recidivists degradation in the performance of their professional work found expression not only in the decrease of systematic work, but also in the shifting from work, requiring certain professional skill, to unskilled labour. This was partly connected with a complete lack of interest in the trade they had learned and above all with degradation due to alcoholism. Not without significance were undoubtedly also difficulties in obtaining a job, connected with prior stays in prison.Those recidivists to whom offences were almost the only source of maintenance, accounted for 17.7%. As many as 19% earned their living partly by committing offences and partly by getting help from their families. Thus, a 'total of over one-third were recidivists who lived above all from offences and work was not their source of income. 29% of the recidivists got the means to cover their expenses through work and by committing offences against property. For 34% of the studied individuals delinquency was most probably not the main source of their income: either they earned their living only through work (16%) or through work and by partly being kept by the family (10%) or they were exclusively maintained by the family (8%). The data gathered indicate that the recidivists studied here were frequently a burden for their families, that many of them had not established a family of their own, those who were married frequently did not perform their duties in regard to their families, and many of the marriages broke up. Their behaviour and relations with the family were characterized by substantial maladjustment to the requirements of family life. The percentage of bachelors among the sampled group was twice as high as is the case with their age group in the whole of Poland’s population of men and amounted to 40%. As many as 20% were divorced and 40% married. But only 20% lived during the period before their last arrest together with their wives; as many as 44% lived with their parents (mainly with their mothers).More than half of the married couples were marked by marital discord. Very bad relations with the wife were often connected with frequent imprisonment of the recidivists, with alcoholism and also the fact that their wives often were women whose personality and mode of life could contribute to the unstability of their married life. The majority of the recidivists completely neglected their children, one-third carried various objects out of the house and afterwards sold them to buy vodka. 18% were convicted of offences harmful to the family. Almost half of them received material help from their families.After release from prison only one-fourths of the studied group can live with their wives. Over half counted on living with their parents and on material help from them, the remaining 25% could not count on anybody's material help, 17% of them even had nowhere to live after their release. While they were at liberty the recidivists studied here drank alcohol as a rule to excess, much more than the average of men does in the towns of Poland. Almost 88% drank at least a quarter of a litre of vodka three times and more a week. The systematic drinking of alcohol to excess was typical not only of the persistent recidivists, of the studied sample, but also of other populations of recidivists studied in Poland.It was found that among this group of recidivists there were manyindividuals, who were alcoholics already at an advanced stage. In the case of 117 of them (53%) a syndrome of symptoms was found, typical of alcoholism. With the majority of them the abstinence syndrome could be established, 21% had gone through an alcohol psychosis.The recidivists started to drink alcohol to excess very early, half of them already before they were 17 years old, 20% at the age of 17—18, 10% from 19—20 years and only 15% — at the age of 21 or later. Combined with the early drinking of alcohol to excess, were distinct symptoms of alcoholism appearing at an early age. They could be noticed with the majority of the alcoholics after at least eight years from the time they had started systematically to drink alcohol to excess. However, this period would be shorter, if one took into consideration the periods of imprisonment, which were for the recidivists enforced breaks in their systematic drinking. In 25% of the recidivists, who were alcoholics, distinct symptoms of alcoholism appeared already at an age below 25 years, 36% — it started between 25 and 27. Symptoms testifying to an advanced stage decreased tolerance and abstinence syndrome appeared according to the recidivists around the age of 27. Systematic drinking of alcohol to excess already at a very early age thus led to early appearance of symptoms of alcoholism. The genesis of the progressive process of demoralization and delinquency, as a rule, had its source not in the abuse of alcohol. Drinking of alcohol to excess usually began already when people started to go astray or to commit offences. Those of the recidivists who drank alcohol to excess from the -time they were still under age, were already at such an early period more socially maladjusted than the remaining recidivists and 'drinking alcohol to excess was at that time one of the elements of their mode of life within a group of demoralized adolescents. For those who started to drink alcohol to excess as young adults (as a rule being also socially maladjusted while still under age), the beginning of abuse of alcohol was often combined with work to earn a living and opportunities to drink at work.Though abuse of alcohol did not play an essential role in the genesis of the process of social maladjustment in the case of this group of persistent recidivists and in the genesis of their delinquency, it nevertheless exerted a distinct influence on the intensification and nature of their further offences. This influence can be noticed in the heterogenity of the offences committed by them and also in the fact that there are only few among the persistent recidivists who have committed offences exclusively against property; connected with the abuse of alcohol is the considerable percentage among the recidivists of those who have committed violent offences. Connected with drinking alcohol to excess are also short periods of being at liberty between the successive convictions. Two categories can be distinguished among the persistent recidivists, where systematic drinking alcohol to excess played a major role regarding their delinquency; this was the group of 41 recidivists, convicted almost exclusively for violent offences in a state of drunkenness and a group of 33 individuals who committed theft while drunk, the motive being as a rule to obtain in this way money to buy alcohol. In the case of the investigated from these two groups, as a rule abuse of alcohol precedes substantially the beginning of delinquency; there are more skilled workers among them, who first used , to work systematically, but later degradation in professional work sets in; among these groups are more recidivists who were first convicted at a later age (above 20 years).Among those who committed petty theft connected with alcoholism, a type of alcoholic already in an advanced stage of alcoholism can be often noticed. He is passive, with a low educational level and a lowered intelligence quotient. Those who commit assaultive offences while drunk,  are especially often characterized by bad tolerance of alcohol; an analysis of the individual cases reveals that the patterns of demoralization of these offenders are most varied.Though 40% of the recidivists who are alcoholics started treatment against alcoholism, while at liberty, they usually gave it up again after a few visits at the outpatient clinics. Only 10% of the alcoholics were treated in psychiatric hospitals in connection with alcoholism; they were sent there because of symptoms of alcoholic psychosis. Dealing with the problem of personality disorders of this group of recidivists the research concentrated on finding answers to the following problems:— whether and in what respect results of the psychological examinations of persistent recidivists differ from the results obtained through studies of the average population and studies of prisoners who are not persistent recidivists. Differences were taken into account in the intelligence level tested with the Wechsler-Bellevue scale and in the personality measured by the MMPI;— what the findings of psychiatric examinations were (examinations to which 59% of the recidivists were subjected);— the setting apart and analysis, on the basis of the entire material, of some of the personality determinants in behavioural deviations of these individuals. The Wechsler-Bellevue scale was administered to 211 of the persistentrecidivists. The results obtained testify to the fact that they markedly differ from 'the average population and the level of their intelligence belongs to the lowest as compared with the results of various other studies of prisoners. As many as 44% of -them had a lower IQ (IQ below 91), 27% were dull (IQ 80—90), 11.8% of boderline intelligence(IQ 66—79) and 5.2% were mentally deficient. The percentage of individuals with the above average intelligence was among those studied here small (9.0%).Though the level of education and the acquired professional qualifications were as a rule very low in the group under investigation, they were particularly low in the case of those recidivists, who had a lowered IQ. The lowered level of intelligence thus made it for many of the recidivists difficult to obtain primary education and to learn a trade. The majority of those with a low level of intelligence were individuals who hadnot even graduated from primary school, who had learned no trade and revealed substantial shortcomings in reading and writing. (As many as 44.5% of those investigated were rather bad in reading and writing). The results obtained through intelligence tests also make one reach the conclusion, that most probably the deterioration of certain intellectual functions noticed with the recidivists under investigation were connected with their alcoholism. Though it was not established (which is in accordance with the results of a number of studies) that the recidivists who revealed symptoms of alcoholism and a lower IQ than the remaining prisoners, it nevertheless was found in the case of alcoholics that more frequently the verbal scale outdistanced the performance scale; besides, tests of alcoholics revealed more frequently profiles with symptoms, according to Wechsler, typical of alcoholics in an advanced stage of alcoholism.No significant differences in intelligence level were found between recidivists, depending on the 'type of offences committed by them. But it was found, that recidivists, who were for the first time convicted when already older than 20 years, revealed a lower IQ than recidivists, who had prior convictions at an earlier age. Among recidivists with a later start of convictions is a particularly large number in the genesis of whose delinquency alcoholism played a role and their inability independently to perform the basic tasks in life, which may be connected also with their low IQ. MMPI was administered to 148 recidivists serving according to its authors’ intentions to evaluate the most important personality traits, influencing the personal and social adjustment. The results obtained indicated marked personality disorders in the case of persistent recidivists as compared with other groups of people, studied with the same inventory, who did not commit offences and did not reveal mental disorders, and also in comparison with prisoners with a lesser degree of social degradation. Among the profiles obtained from these recidivists very frequently high-ranging profiles could be found (48%), where at least one scale reached 81—100 points.High profiles were rarely found in other Polish research. The average profile of the recidivists studied here shows a predominance of scale 6 (Pa) and 4 (Pd) and high too are scales 8 (Sc) and 2 (D), pointing to considerable hostility on the part of the sampled individuals, their suspicious attitude to and lack of confidence in their environment, irritability, shallowness of emotional reactions, alienation, lack of positive family ties and defiance of moral norms.Typical of this group is also a considerable moodiness, low self-esteem, lack of belief in one’s own possibilities and mental demobilization. The average profile of this group is similar to a psychopatic profile, but (as is the case in certain other Polish studies of prisoners) with a substantial paranoid and schizoid component.The results obtained point to greater personality disorders in recidivists, revealing symptoms of alcoholism than in those, where such symptoms were not found. Alcoholics obtained higher scores than non-alcoholics in all the clinical scales. There were, however, found no differences in the shape of the mean profile, which in both compared groups is similar and characterized by elevation of the same scales. Alcoholics revealed higher scores in all the scales; the differences noticed reached a level of statistical significance in all the scales with the exception of scales 4 (Pd) and 2 (D). This result is interesting, because in various foreign studies on alcoholics it was found that precisely these two scales differentiated in a statistically significant manner in the case of alcoholics and non-alcoholics. But in the population of persistent recidivists, characterized in general by marked psycho-social maladjustment, dating back to childhood, and alcoholism of some of them has its roots in this maladjustment, it was found, that alcoholics failed to differ significantly from non-alcoholics in scale 4 (Pd). The life situation of all the recidivists studied (within prison walls because of convictions) undoubtedly exerted its influence on the scores in scale 2 (D), in the case of alcoholics as well as non-alcoholics. Expert psychiatric opinions (regarding various periods of the life of the persistent recidivists) and/or results of psychiatric examinations conducted during this survey were collected for 60% of the cases. These data show that only in 10% of the examined recidivists neither personality disorders nor any other mental disorders were found. In as many as 70% of the recidivists, subjected to psychiatric expert examination, personality disorders of various etiology were discovered: psychopathy in 48%, encephalopathy in 22%; in 40% alcoholism was found, appearing as such or jointly with other disorders.Data regarding the remaining recidivists, not embraced by psychiatric examinations, indicate, that the majority (as many as 63%) of them were marked by advanced alcoholism, or had suffered from brain damage or psychological examinations revealed mental deficiency. After having studied data related to the remaining 37% of cases not subjected to psychiatric examination, it turned out, that though the above mentioned disorders were not found, nevertheless the majority of them were people, whose behaviour was marked by considerable agressiveness as well as self-aggression and only in 9% of the recidivists, not subjected to psychiatric examinations, no such behaviour patterns were found.The entire information about all the prisoners who were persistent recidivists — those who underwent psychiatric examinations as well as those who did not — indicates that individuals who revealed no distinct psychopathological symptoms are rare among them, amounting according to estimates to around 10% (taking into account the established percentage among those who underwent psychiatric examinations), and to 20%, if one would take into consideration also data about recidivists who underwent no psychiatric examinations, taking into account their mental deficiency, alcoholism and brain damage. The last mentioned percentage (20%) would, however, decrease markedly, if one would take into account data about certain behavioural disturbances of the recidivists, above all about their aggressiveness and self-aggression. When discussing the entire material special attention should be drawn to the fact that in one-fifth of the group encephalopathy (disturbances connected with brain damage) was diagnosed and in another 9% encephalopathy was suspected, since it was 'to a considerable degree justified by the entire aspect of the data stemming from the interview. In additional 25% it was found during interviews that they had suffered from concussions of the skull, combined with loss of consciousness. But in these cases (there nevertheless, was a lack of sufficient data, confirming this information.Data regarding the age at which the recidivists suffered from brain damage or diseases of the central nervous system indicate, that in the case of 40% of them such diseases took place during the earlier period of their - life (complications of delivery, traumas or meningitis at preschool age), with only one-third it occurred when they were already young adults or adults. Those recidivists who suffered from brain damage,frequently distinguished themselves by substantial impulsiveness, they were aggressive, committed acts of self-aggression and badly adjusted to prison conditions. Thus, those who had suffered from brain damage obviously had difficulties in social adjustment. However, with approximately half of those who had suffered such damage, the process of social maladjustment had already begun before they had suffered such damage. On the basis of the entire aspect of data about the behaviour of the recidivists during various periods of their life — in prison as well as at liberty — a psychopathological characteristic outline was drawn up for each one of them. Included in this characteristic outline were those personality traits appearing with special intensity, which according to the psychologists, conducting the survey in prison, were of special significance for social maladjustment in each case. A comparison of the above-mentioned characteristic traits yielded a picture, similar to that obtained in surveys conducted with MMPI. The majority of the recidivists were defined as touchy, quick-tempered, incapable to make systematic efforts, with insufficient resistance to cope with the difficulties of life. They often revealed a deep conviction of having been wronged and in connection with this strong resentment, directed against their environment. As many as 45% of the recidivists were defined as showing substantial disturbances in their emotional attitude towards their surroundings: of these 29% — as being unable to establish lasting, positive emotional ties with their milieu, 16% had completely broken all ties with their nearest family, due to intensified conflicts with them. Relatively frequently (52%) could be isolated a type of a passive recidivist whose passivity was partly being explained by his constant lack of achievements, not only in the sphere of approved social activity, but also in the sphere of delinquency. 59% revealed marked impulsiveness; these were individuals, whose behaviour was characterized by shortrange activity, without any more distant goals, lack of giving any thought to the consequences of their own conduct, an attitude aimed at getting temporary, immediate pleasure out of it. The impulsiveness was particulary striking in two types of behaviour patterns: in aggression and self -aggression. Three-fourths of the recidivists were defined as aggressive (such who time and again, in various situations and in regard to various individuals had behaved aggressively and those who revealed generalized, great hostility). Among the aggressive ones one-third were those, who behaved aggressively only when /not sober. In the case of a considerable part of the aggressive individuals information about their aggressiveness was from a period, when they were still of school age. More frequently aggressive were those who showed symptoms of alcoholism than those who did not. Frequently, acts of self-aggression were sombined with aggressiveness. Acts of self-aggression were committed by 56%. Many of such acts were not some specific reaction to prison situations, the majority of the perpetrators had committed acts of self-aggression while at liberty (28% of them committed self-aggression only when at liberty, 41% — while at liberty and in prison, too). More frequently alcoholics committed acts of self -aggression than those who showed no symptoms of alcoholism. The biographies of recidivists indicate that significant for the genesis and the deepening of their social maladjustment was a negative family milieu, during their childhood as well as personality disorders revealed by them, which grew in intensity in connection with later experiences in life and also with their alcoholism. A comparison of persistent recidivists, coming from families, evaluated as negative, with the remaining persistent recidivists, revealed a number of essential differences among them. Recidivists from negative family milieux began more frequently to commit theft while still under age, more frequently revealed aggressiveness during their school period, more often did not graduate primary school, began at an especially early age to drink alcohol to excess. In individuals brought up in a negative atmosphere and deprived of care, the early symptoms of maladjustment revealed considerable durability.Alcoholism — having its roots in the social maladjustment of the recidivists studied here — deepened existing disorders, proof of which are the results, presented above, pointing to lowering of certain intellectual functions with some of them and personality disorders in the case of those recidivists who showed symptoms of alcoholism. This testifies to the fact that alcoholics were more frequently marked by passivity, impulsiveness in action, aggressiveness and self-aggression.The data collected indicate that multiple stays in prison intensified the alienation of the recidivists and hampered their attempts at social readjustment.  Imprisonment weakened the anyhow already weak ties with the family and limited their social contacts to other prisoners only. In regard to the prison officers the recidivists revealed considerable hostility, which, as it seems, could not remain without an influence on their attitude towards other people representing the authorities. Though terms meant for 'the persistent recidivists a compulsory break in prison drinking, this, however, did not prevent, as results from their statements, the further drinking of alcohol to excess immediately after their release from prison. These studies reveal that persistent recidivists are not a homogeneous population. There could be noticed distinct differences between those among them (who account for 70.4%) who had early convictions after the age of 17, when still being young adults and those (29.6%) who had their first conviction at a later age, when 21 years old and more. Those “late” recidivists are less socially degraded, they committed rather petty offences, most frequently connected with drinking alcohol to excess.Though the “late” recidivists do not suffer substantially from the “early” recidivists as regards the number of those showing symptoms of alcoholism and though they started later th&n the “early” offenders to drink too much alcohol, there nevertheless are more individuals among them, whose delinquency is already of a secondary nature, making its appearance in their life later than systematic abuse of alcohol. In the case of “late” recidivists it was found more often than in that of “early” ones that they had a lower IQ, but there were among them fewer individuals considered aggressive and more rarely individuals guilty of self-aggresion.The data presented before, point to the heterogeneity of the offences committed by persistent recidivists. First of all there should be set apart among the recidivists those (approximately one-fourth of the total) who, on the basis of the offences committed by them may be listed as “serious” and the remaining ones who should rather be considered perpetrators of petty offences. In addition to this there can be set apart 27% of the perpetrators of offences exclusively against property and 9% of recidivists who were exclusively guilty of offences against the person. The majority of the recidivists were, however, the perpetrators or a variety of offences, which was undoubtedly due to drinking alcohol to excess. Those who committed theft, under 'the influence of alcohol committed assaults, some of those who committed offences against the person started in connection with their growing habit of drinking alcohol to excess, to steal, in order to obtain the money needed for alcohol. Though the abuse of alcohol effaced the differences of delinquency of the various categories of recidivists, it was possible to establish that those among them, who committed exclusively or mainly offences against the person (27.6%) more frequently had in the past suffered from brain damage. Those individuals studied, who were almost exclusively perpetrators of offences of an assaultive nature (18.7%), differed from the remaining ones by an essentially smaller degree of social maladjustment, the later start of delinquency (more often only above the age of 20), by more systematic work at 'the time they were still adolescents, and the fact that more often they had learned a trade and spent less time in prison. Often poor alcohol tolerance was found with these individuals. Proof of the heterogeneous nature of the population of persistent recidivists are the results, pointing to the significant differences among those of them, who were convicted for the first time when above twenty years old and those, who were brought before a court and convicted much earlier, between the perpetrators of offences against the person and the remaining persistent recidivists. To the heterogenous features of the examined population point also the previously mentioned results, indicating significant differences among recidivists, revealing symptoms of alcoholism and those where such symptoms were not found.